Modernitas Dan Perubahan Nilai Dalam Kesenian Kuda Lumping: Studi Kasus Kelompok Margi Wijaya Di Desa Asinan, Kabupaten Semarang - Dina Islamiyah; Fina Idamatu Rizqi; Elfio Adistya Putri Ardani; Laila Nur Afwa Alamien; Fauzan Syahru Ramadhan (PANALUNGTIK, 2025)
This article focuses on the value shifts in the traditional art of Kuda Lumping as a result of the influence of modernity, by taking a case study of the Margi Wijaya art group in Asinan Village, Semarang Regency. The purpose of this article is to find out the changes in performance elements such as music, costumes, and dance movements that have undergone significant transformations to suit the tastes and interests of today's audiences. This research uses field observation and historical methods to trace the process of change over time. The observation method is carried out directly to the field then combined with the historical method consisting of heuristics, criticism, interpretation, and historiography. The results showed that traditional gamelan-based music began to be replaced with electronic music that was more rhythmic and attractive. Dancer costumes, which were originally simple and full of symbolic meaning, are now more colourful and modern. Dance movements have also been adjusted to be more dynamic and entertaining. These changes reflect a shift in values from religious and traditional orientations towards entertainment and popular aesthetics. Nevertheless, the Margi Wijaya group still tries to maintain traditional elements as local cultural identity. This study shows that traditional arts are not completely extinct in the flow of modernity but are transformed through an ongoing process of adaptation and value negotiation.